CLINICAL AND LABORATORY CHARACTERISTICS OF PREECLAMPSIA IN PREGNANT WOMEN WITH UNDERLYING MEDICAL CONDITIONS AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY FROM 2023 TO 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and laboratory characteristics of preeclampsia in pregnant women with underlying medical conditions.Methods: A cross-sectional descriptive study was conducted on 205 eligible participants at National Hospital of Obstetrics and Gynecology from January 2023 to December 2025.Results: The mean maternal age was 33.86 ± 5.86 years. Severe preeclampsia accounted for the majority of cases (80.98%). Statistically significant differences were observed between the severe preeclampsia group and the non-severe group regarding urea, AST, ALT, LDH, MHVC, and fetal birth weight. Hypertension was the most common underlying comorbidity and was significantly associated with preeclampsia (OR = 3.12; p < 0.05).Conclusion: Severe preeclampsia accounted for a high proportion of cases. Hypertension was the most common chronic comorbidity and may contribute to the increased risk and severity of preeclampsia, along with other underlying medical conditions.
Keywords: Preeclampsia, underlying medical conditions, clinical characteristics, laboratory findings.